PEG-aspargase and DEP regimen combination therapy for refractory Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis. Issue 1 (December 2016) - Wang, Jingshi; Wang, Yini; Wu, Lin; Zhang, Jia; Lai, Wenyuan; Wang, Zhao
Abstract Background Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is the most frequent subtype of secondary HLH triggered by infections. Previous studies have shown that ~30 % or more of patients with EBV-HLH do not respond to standard therapy. This study investigated the efficacy and safety profile of a modified DEP regimen in combination with PEG-aspargase (L-DEP) as a salvage therapy for refractory EBV-HLH. Methods In this study from October 2014 to October 2015, 28 patients with refractory EBV-HLH received a L-DEP regimen at the Beijing Friendship Hospital, Capital Medical University. Treatment efficacy and adverse events were evaluated at 2 and 4 weeks after L-DEP treatment. Results Median EBV-DNA concentrations before and 2 weeks after receiving the L-DEP regimen were 9.6 × 105 (1.5 × 104  − 1 × 109 ) copies/mL and 2.2 × 105 (3.8 × 102  − 1.2 × 107 ) copies/mL, respectively; the post-treatment values were significantly lower than that of the pretreatment (P  = 0.048). Nine of the 28 study patients achieved complete response (CR) and 15 partial response (PR), resulting in an overall response rate of 85.7 % (CR+PR). Four patients who did not achieve response died within 4 weeks of receiving L-DEP. Thirteen of the 24 patients who achieved partial or complete response received subsequent allogenic hematopoietic stem cell transplantation (allo-HSCT). Ten of these 13 patients survived until 1 March 2016. The major adverse effects of the L-DEP regimen were high serum amylase concentrations, abnormal liver function, and coagulation disorders. Conclusions This study suggests that L-DEP is a safe and effective salvage therapy prior to allo-HSCT for refractory EBV-HLH and increases the possibility of such patients receiving allo-HSCT. A prospective multicenter large-scale clinical trial that aims to validate the L-DEP regimen for refractory EBV-HLH is currently underway (ClinicalTrails.gov Identifier: NCT02631109).